Proposal of Suitable Control System and Measure in Internal Logistic Process - Kučera, Tomáš; Švadlenková Groulová, Veronika (Kaunas University of Technology, 2021)
In order to choose the right procedure for optimizing production processes, it is necessary to get acquainted with the issues of logistics, logistic operations and modern logistic methods. Today, the term logistics is used in all companies and industries. The automotive industry is one of the fields in which special emphasis is placed on understanding proper logistics and all its sectors. Its understanding and penetration into the depth of its essence is key to succeeding in the market in leadership positions and leads to gaining new customers, retaining existing customers, saving time and thus increasing the company's financial stability in the existing market. The article addresses the issue of reducing errors at the beginning of the production of individual bus parts and proposes the introduction of new control systems for employees. The aim of the article is to propose a suitable system and measure in the internal logistic process in a manufacturing company. The article is based on research of world literature, in-depth interviews with top managers in a manufacturing company, detailed analysis of internal data of a manufacturing company and analysis of the working environment of employees.
Návrh vhodného kontrolního systému a opatření v interním logistickém procesu
Keywords: internal logistic process; suitable system and measure; control systems; modern logistic methods; interní logistický proces; vhodný systém a opatření; řídicí systémy; moderní logistické metody